Application of Octenidine into Nasal Vestibules Does Not Influence SARS-CoV-2 Detection via PCR or Antigen Test Methods - Ojan Assadian; Fabiola Sigmund; Daniela Herzog; Karin Riedl; Christoph Klaus (MDPI AG, 2023)
The targeted or universal decolonization of patients through octenidine for nasal treatment and antiseptic body wash for 3 to 5 days prior elective surgery has been implemented in several surgical disciplines in order to significantly reduce surgical site infections (SSIs) caused by Staphylococcus aureus carriage. However, as most healthcare facilities also screen patients on admission for pilot infection, it is imperative that a prophylactic nasal decolonization procedure not yield a false negative SARS-CoV-2 status in otherwise positive patients. We assessed the effect of a commercially available octenidine-containing nasal gel on two different screening methods-antigen (Ag) detection based on colloidal gold immunochromatography and RT-PCR-in a prospective-type accuracy pilot study in asymptomatic SARS-CoV-2-positive inpatients. All patients still showed a positive test result after using the octenidine-containing nasal gel for about 3 days; therefore, its application did not influence SARS-CoV-2 screening, which is of high clinical relevance. Of note is that Ag detection was less sensitive, regardless of the presence of octenidine. From an infection prevention perspective, these results favor octenidine-based decolonization strategies, even during seasonal SARS-CoV-2 periods. As only asymptomatic patients are considered for elective interventions, screening programs based on RT-PCR technology should be preferred.